RHETORICAL MOVES ON THE BBC NEWS ABOUT THE UNITED STATES OF AMERICAN PRESIDENT, JOSEPH BIDEN, IN ANNOUNCING OF OIL BANNING OVER UKRAINE - Ali - Amran (VISION, 2022)
The objective of this study is to find out the functions of rhetocial moves and to find out the negative effects of rhetorical moves by Josep Biden. This research used the qualitative design. The data source of this research is the script that will be taken from Youtube channel. The channel containes news about the United States of American President, Joseph Biden, in announcing of oil banning over Ukraine conflict.The research shows that there are three distinct registers, namely the "formal," "consultative," and "casual" registers. The formal register predominates by a factor of 19% over any other. The objective of this formal register is to facilitate communication. Many individuals continue to be ill-equipped with register skills. They are unsure of how to properly construct sentences. They are hesitant to use such language. However, the register experiment will teach us how to use register effectively.